Cancer stem cells as 'units of selection'. (23rd October 2012) - Greaves, Mel
Abstract Cancer development is widely recognized to be a somatic cell evolutionary process with complex dynamics and highly variable time frames. Variant cells and descendent subclones gain competitive advantage via their fitness in relation to micro‐environmental selective pressures. In this context, the 'unit' of selection is the cell, but not any cell. The so‐called 'cancer stem cells' have the essential properties required to function as the key units of selection, particularly with respect to their proliferative potential and longevity. These cells drive evolutionary progression of disease and provide reservoirs for relapse or recurrence and drug resistance. They represent the prime, but elusive and moving, targets for therapeutic control.